Control of Systemic Iron Homeostasis by the 3' Iron-Responsive Element of Divalent Metal Transporter 1 in Mice. Issue 5 (23rd October 2020) - Tybl, Elisabeth; Gunshin, Hiromi; Gupta, Sanjay; Barrientos, Tomasa; Bonadonna, Michael; Celma Nos, Ferran; Palais, Gael; Karim, Zoubida; Sanchez, Mayka; Andrews, Nancy C.; Galy, Bruno
Abstract : Supplemental Digital Content is available in the text